Advantages of balance scorecard in the public sector (2014)
The implementation of a system of indicators for administration by the National Bureau of Statistics - DANE, using the methodology of Balanced Scorecard BSC or balanced scorecard is a management model that translates the strategy into interrelated objectives, measurable through indicators and linked to action plans that align the behavior and actions of all members of the organization. The BSC part of the vision and strategies of the organization. From there the required strategic objectives are defined to achieve the vision, and these in turn will result from the mechanisms and strategies that govern our results with internal and external customers. Internal processes are planned to meet the financial requirements and the customer. Finally, the methodology recognizes that learning and growth is the platform on which rests the whole system and where the objectives are defined for this perspective. Also the application of this methodology will allow to evaluate the performance of each area through indicators detailed in the Scorecard and the analysis of these indicators can see how committed are the areas with the fulfillment of the institutional mission.